Factors Associated with Persistent malaria transmission in urban Peripheral Areas Dar es Salaam Region, Tanzania - Charles, D Mwalimu; Janneth, Mghamba; Ally, Mohamed; Ally, Hussein; Ahamed, Abade; Merycelina, Mubi (Journal of Public Health International, 2020)
Africa Region has the highest burden of malaria with an estimated of 3.5 million more malaria cases in 2017 compared 212 million cases in reported in 2016. Data collected from 2015 to 2017, shown no global progress in reducing malaria cases. In Mainland Tanzania, malaria control interventions have significantly led to the reduction in malaria prevalence from 18.1% in 2008 to 7.3% in 2017. Despite of these achievements, malaria burden is still highly heterogonous with some regions including urban peripheral areas of Dar es Salaam, presenting persistent malaria transmission ranging from 2 to 57%. Material and Methods A cross- sectional population based survey was carried out in Ilala Municipality in Dar es Salaam; data was collected from 2nd to 31 April, 2019. Multistage cluster sampling was used to select the households where individual member were conveniently selected to participate in the study. Structured questionnaire were administered by the trained researcher assistants to assess individual risk factors for malaria. Rapid Malaria diagnostic test (mRDT) was used to identify individual exposed to malaria infection. Measure of association used was prevalence odds ratio (POR). Multivariate regression model used to determine prevalence odds ratio, variable with p- value < 0.05 were considered as independent risk factor for persistent malaria transmission. Results A total of 830 participants were recruited in the study, mean age was 24yrs ±20.4SD. Majority 489 (58.9%) were female, 459 (55.3%) were >18 yrs old, primary or no education were 687 (82.8%), farmer or unemployed were 639 (77%). Msongola ward contributed 406 (48.9%). Overall malaria prevalence in the study areas was (4.5%). Nets ownership was 141 (16.9%), usage was 121 (85.8%).Low proportion of net ownerships (POR: 7.67, 95% CI: 4.23, 24.6), residing in the households surrounded by mosquito breeding sites POR: 20.07, 95% CI: 7.03, 57.29) and residing in houses with unscreened windows (POR: 1.21, 95% CI: 1.26, 3.40) were independently associated with malaria infection. Conclusion Low nets ownership, residing in the households surrounded by mosquito breeding sites and in households with unscreened windows was independent factors associated with risk of malaria in the areas. Promotion of ITNs coverage, application of biolarvicides through community engagement and house screening was recommended to reduce the risk of malaria infection in the areas.
Keywords: Persistent Malaria; Transmission; Risk factors; Peripheral areas; Dar es Salaam Tanzania.